Nauczyciele etyki o swoich kwalifikacjach, kształceniu i doskonaleniu zawodowym - Madalińska-Michalak, Joanna (Studia Edukacyjne, 2018)
This paper considers teachers of ‘ethics’, which is a relatively new curriculum subject in school education in Poland. The paper focuses on the assessment of formal requirements for ethics teachers and on the evaluation of teacher education for teachers of ethics in Polish schools. The paper includes analysis of the perspectives of teachers of ethics concerning the future development of teacher education programs. The paper reports on a study of the place of ethics as a curriculum subject and on the practice of teaching ethics in schools in Poland. The study derives from a larger project completed between 2014-2016 and entitled ‘Ethics in the Systems of Education in Poland and Selected Western Countries (Germany, United Kingdom, Spain, Portugal, France, USA, Norway, Finland)’. The project was implemented under the National Program for the Development of Humanities of the Polish Ministry of Science and Higher Education. The project was conceived as a contribution to educational research and knowledge on the teaching of ethics in the school system and to the building of ethics as a school subject in the Polish school system.